2022
DOI: 10.3389/fonc.2022.1022496
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of pembrolizumab plus vemurafenib and cobimetinib in patients with metastatic melanoma

Abstract: BackgroundPreclinical and translational evidence suggest BRAF/MEK inhibitors modulate the tumor microenvironment (TME), providing rationale for combination with immunotherapy.MethodsThis investigator-initiated, phase I trial evaluated pembrolizumab, vemurafenib, and cobimetinib in patients with untreated, BRAFV600E/K mutant advanced melanoma. The first 4 patients received vemurafenib with pembrolizumab, and the next 5 patients received vemurafenib and cobimetinib with pembrolizumab. Primary endpoints: safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The second interim analysis of the IMspire150 study showed no significant improvement in OS with triplet therapy (atezolizumab, cobimetinib, and vemurafenib) compared with MEK/BRAF kinase inhibition alone [ 12 ] and, in the phase 3 COMBI-i study, the addition of the PD-1 inhibitor spartalizumab to trametinib plus dabrafenib did not significantly improve PFS and led to increased toxicity compared with trametinib plus dabrafenib [ 22 ]. In a phase 1 study, DLTs of dermatitis (n = 5), QTc prolongation (n = 1), and arthralgias (n = 1) were reported among 5 patients treated with the triplet combination of pembrolizumab, cobimetinib, and vemurafenib, and the safety findings led to early closure of the study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second interim analysis of the IMspire150 study showed no significant improvement in OS with triplet therapy (atezolizumab, cobimetinib, and vemurafenib) compared with MEK/BRAF kinase inhibition alone [ 12 ] and, in the phase 3 COMBI-i study, the addition of the PD-1 inhibitor spartalizumab to trametinib plus dabrafenib did not significantly improve PFS and led to increased toxicity compared with trametinib plus dabrafenib [ 22 ]. In a phase 1 study, DLTs of dermatitis (n = 5), QTc prolongation (n = 1), and arthralgias (n = 1) were reported among 5 patients treated with the triplet combination of pembrolizumab, cobimetinib, and vemurafenib, and the safety findings led to early closure of the study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIT is advantageous as it is administered to a single, localized tumor region, minimizing the chances of detrimental off‐target toxicity, immune‐related adverse events, or cutaneous adverse events, all of which are challenges faced by the systemic therapies used for melanoma treatment, such as chemotherapy, targeted therapy, or immunotherapy 44 . Due to the significant adverse events of combining targeted therapy and ICB, a phase I clinical trial has faced early closure, 45 and another phase II trial experienced grade 3–5 treatment‐related adverse effects in 70% of the combined treatment arm patients 46 . Further, chemotherapy is notorious for immunosuppression, making it a poor candidate to be combined with ICB 47 and, due to poor response rates, chemotherapy has not been the recommended standard for melanoma management since the development of targeted and immunotherapy options 48 .…”
Section: Photoimmunotherapy (Pit)mentioning
confidence: 99%
“…There were two groups treated with pembrolizumab/vemurafenib and pembrolizumab/ vemurafenib/cobimetinib, respectively. The median OS was 23.8 months for vemurafenib/pembrolizumab, while the triple combination did not allow the calculation of the OS as it was discontinued due to the occurrence of side effects, leading to the closure of the study [23]. BRAF inhibitors (BRAFi) appear to be able to modulate the tumor microenvironment (TME).…”
Section: Pembrolizumab and Associationsmentioning
confidence: 99%
“…BRAF inhibitors (BRAFi) appear to be able to modulate the tumor microenvironment (TME). In fact, on the one hand, the administration of a BRAFi in a BRAF-mutant melanoma model resulted in increased expression of CD40 ligand and interferon-gamma on tumor-infiltrating CD4+ lymphocytes (TILs) and decreased T-reg and myeloid cells on the other hand, suggesting antitumor modulation of the TME [23]. Furthermore, an increase in the T-cell exhaustion markers TIM-3 and PD1 was correlated with BRAFi in patients with metastatic melanoma [23].…”
Section: Pembrolizumab and Associationsmentioning
confidence: 99%
See 1 more Smart Citation